Tinjauan Kuat Tekan Dan Kuat Lentur Dinding Panel Batu Bata Merah Dengan Perkuatan Tulangan Bambu - Baskoro, Ifandi; , Muhammad Ujianto, S.T., M.T (2016)
In general, the wall made of stone or brick are coated with mortar, in large volume and location of buildings in areas that require special treatment, such as earthquakes and storied building. Wall panel is one of the technological developments in the field of precast concrete. Precast wall is not a structural element. The aim of this research in order to become an alternative to conventional wall that is more practical and efficient to costs and time. Specufication wall panels wear fas: 0.5, fine aggregate and cement ratio 1: 4. In research done in the manufacture of test specimens with mortar cubes dimension 5cmx 5cm and wall panel using bamboo reinforcement with a dimension of 100 cm x 50 cm x 10 cm. This research is testing compressive and flexural strength of wall panels. Mortar cubes specimen were tested tap obtained yield was 2.65 MPa. The value of compressive strength test wall panel is 1.878 MPa (without reinforcement) and 2.109 MPa (with reinforcement) increased 12,300% of the wall panel without reinforcement, then testing the flexural strength was obtained for 1,493 MPa (without reinforcement) and 3.080 MPa (with reinforcement) an increase of 106,296%.